Mapping the underside of an iceberg with a modified underwater glider - Zhou, Mingxi; Bachmayer, Ralf; deYoung, Brad (Journal of Field Robotics, 2019)
Icebergs pose many challenges to offshore operations in the Arctic Ocean and sub-arctic regions. They could damage underwater infrastructure such as pipelines, and disrupt marine transportation. The below-water shape of an iceberg is a key factor for iceberg management in the North Atlantic Ocean because it affects the iceberg towing plans and iceberg drift patterns. In recent years, unmanned platforms have been proposed as potential candidates for underwater iceberg mapping. Compared to a conventional ship-based iceberg survey, using unmanned platforms is more efficient and safer. In this paper, we present research using a hybrid underwater glider to measure the underwater shape of an iceberg. The vehicle is equipped with a mechanical scanning sonar for range sensing and iceberg mapping, and a guidance system is designed to use the sonar measurements for guiding the vehicle to circumnavigate an iceberg at the desired standoff distance. Several field experiments have been conducted on an iceberg to evaluate the system performance. With repeated observations, the underside of the target iceberg was successfully reconstructed, and iceberg shape comparisons are presented.